2011
DOI: 10.1371/journal.pone.0019475
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Neoangiogenesis and Follicle Survival by Sphingosine-1-Phosphate in Human Ovarian Tissue Xenotransplants

Abstract: Ovarian transplantation is one of the key approaches to restoring fertility in women who became menopausal as a result of cancer treatments. A major limitation of human ovarian transplants is massive follicular loss during revascularization. Here we investigated whether sphingosine-1-phosphate or its receptor agonists could enhance neoangiogenesis and follicle survival in ovarian transplants in a xenograft model. Human ovarian tissue xenografts in severe-combined-immunodeficient mice were treated with sphingos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 56 publications
4
137
0
4
Order By: Relevance
“…Validating and confirming in vitro organ culture experiments, doxorubicin treatment also resulted in reduced vascular density in xenografted human ovarian tissues compared with controls. These results are consistent with other studies that have demonstrated that chemotherapy may induce stromal fibrosis and o varian vascular abnormalities [18,21].While it is challenging to demonstrate that vascular damage directly contributes to chemotherapy-induced ovarian damage, in a recent study we showed an inverse correlation between ovarian vascular density and primordial follicles apoptosis [22]. It is normally supposed that primordial follicles do not depend on blood perfusion, but clinical experience from ovarian tissue transplantation do not support this belief [5].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Validating and confirming in vitro organ culture experiments, doxorubicin treatment also resulted in reduced vascular density in xenografted human ovarian tissues compared with controls. These results are consistent with other studies that have demonstrated that chemotherapy may induce stromal fibrosis and o varian vascular abnormalities [18,21].While it is challenging to demonstrate that vascular damage directly contributes to chemotherapy-induced ovarian damage, in a recent study we showed an inverse correlation between ovarian vascular density and primordial follicles apoptosis [22]. It is normally supposed that primordial follicles do not depend on blood perfusion, but clinical experience from ovarian tissue transplantation do not support this belief [5].…”
supporting
confidence: 93%
“…While it is challenging to demonstrate that vascular damage directly contributes to chemotherapy-induced ovarian damage, in a recent study we showed an inverse correlation between ovarian vascular density and primordial follicles apoptosis [22]. It is normally supposed that primordial follicles do not depend on blood perfusion, but clinical experience from ovarian tissue transplantation do not support this belief [5].…”
Section: • Impact Of Chemotherapy On Stromal/vascular Function In Ovarymentioning
confidence: 85%
“…Examine the possible presence of malignant cells in ovarian cortex from patients with tumors after xenografting of the ovarian tissue into host [21,22], analyze follicular developmental potential [23], discuss oocyte quality and ovarian histology and function after cryopreservation [24,25], investigate the methods improving ovarian function and reducing apoptosis after transplantation [20,26,27]. In our study, the ovarian xenotransplantation used pharmacological angiogenic factor in a rabbit model to improve angiogenesis after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In this controlled study, it is noteworthy that untreated xenografted animals showed a normal uterine development, whereas those xenografted and treated with gonadotropins, triptorelin, or both, showed underdevelopment [78]. Other substances such as the anti-apoptotic S1P and angiogenic factors, such as VEGF, are currently under scrutiny to establish if they could improve the immediate post-transplant follicular loss [87][88][89].…”
Section: Ovarian Cortical Tissue Transplantmentioning
confidence: 91%